Event-triggered composite adaptive fuzzy control of sailboat with heeling constraint. (1st September 2020) - Deng, Yingjie; Zhang, Xianku; Zhang, Qiang; Hu, Yancai
Abstract: In this paper, the event-triggered composite adaptive fuzzy control laws are developed to control both the surge speed and the heading angle of the sailboat. The fuzzy logic systems (FLSs) are employed to approximate the nonlinearities in the model of the sailboat. To enhance the approximating accuracy, a serial–parallel estimation model is established at first, and the composite adaptive laws of the FLS weights are then derived by combining the tracking errors with the prediction errors between the estimation model and the dynamic loop of the sailboat. To prevent the sailboat from capsizing, we consider the heeling constraint in the roll motion during the voyage. By using the backstepping method, the heeling constraint is transformed to the input saturation of the sail. The auxiliary systems are fabricated to offset the input saturation of the sail and the rudder, which are incorporated into the control laws. To reduce the acting frequencies of the actuators, the control laws for the sail and the rudder are designed in the event-triggered form, and the triggering conditions are constructed separately. The uncertain gain of the rudder is estimated by the adaptive laws. The proposed control scheme can guarantee the semi-global uniformly ultimate boundedness (SGUUB) of all the errors. Through the numerical path-following test, the effectiveness of the proposed scheme is verified. Highlights: A unified composite adaptive fuzzy control frame is proposed for the sailboat. The heeling constraint is considered in the control. The saturation constraints are offset by the auxiliary systems. The uncertain gain of the rudder is estimated by the adaptive laws. The event-triggered control is adopted to reduce the acting frequencies of the actuators.